An [Fe‐Fe]‐Hydrogenase Mimic Immobilized on MCM‐41 for the Photochemical Production of Hydrogen in Pure Water. Issue 6 (22nd April 2014) - Wang, Wen; Yu, Tianjun; Zeng, Yi; Chen, Jinping; Li, Yi
Abstract A composite proton‐reducing catalyst Hy@MCM‐41 was created by using a hydrophobic [Fe‐Fe]‐hydrogenase mimic (Hy) incorporated into the K+‐exchanged molecular sieve MCM‐41. Hy acts as the active site to generate H2 by reducing H+, and MCM‐41 provide a large surface area to maintain the dispersion of Hy and to prevent aggregation and precipitation. Hy@MCM‐41 was successfully applied to the light‐induced hydrogen production in pure water with an iridium compound [Ir(ppy)2bpy]Cl and triethylamine (TEA) as the photosensitizer and the sacrificial electron donor, respectively, exhibiting good stability and catalytic activity. The present study provides a general strategy for the application of water‐insoluble catalysts in pure water by using mesoporous molecular sieves.